Estudio para la creación y funcionamiento de una cooperativa de ahorro y crédito al servicio del sector productivo y comercial del cantón Balzar – provincia del Guayas, año 2013 - Rizzo Holguín, Karen Melissa (2013)
This research work was carried out by the productive sector and commercial Balzar Canton, located north of the province, where most of its inhabitants are engaged in agriculture and business, and then carry out a survey to find out their current activities was found that in recent years has seen a huge increase in economic activities. Which is why it became necessary a feasibility study to enable the creation of a Savings and Credit Cooperative in this location, to provide microcredit to all who request it and thus improve the quality of life of its inhabitants. The realization of this project, a study was initiated with the local financial system, and the only existing cooperative in Canton, and then turn to the legal basis is the process for the creation of the cooperative, the designated legal by the Superintendence of popular and solidarity economy and the number of members that constitute it. To develop this work we used the inductive-deductive method, which allowed collecting information through qualitative and quantitative research, based on the observation of facts, based on the survey, and then get to the exploration and interpretation of results. After the market study proceeded to perform the analysis of supply and demand, and then meet the legal supply, with all the requirements required by the Agency to the leads, and then pass the technical study, the organization of business, economic and financial study of the new institution to be created in the city town. In conclusion we designed a financial plan that identified the importance of creating a new financial institution in this town, giving recommendations for this entity provide excellent service to all citizens.